(untitled) (The Review of Diabetic Studies, 2025)
Background: HCAIs remain one of the biggest challenges facing critical care units in terms of increased mortality and high healthcare and morbidity cost. Nursing staff can play a vital role in infection prevention; however, there are still a number of knowledge gaps and inconsistencies in adhering to evidence-based practice. The aim of this study, therefore, will be to establish whether a structured educational intervention can affect the practices of nursing staff in relation to the prevention of HCAI within a critical care unit. Methods: A quasi-experimental pre-test/post-test design was used that included a sample of 110 nursing personnel (68 registered nurses and 42 nursing technicians) caring for patients in the medical-surgical intensive care unit. Data collection was through a validated knowledge assessment tool and observational checklist at baseline, immediately post-intervention, and at 3-month follow-up. HCAI rates were also monitored across the study period. Results: Significant improvements were seen in nursing knowledge scores: pre-intervention, 60.1 ± 9.4; post-intervention, 82.3 ± 7.1; p < 0.001. Knowledge gains were consistent across both professional roles. Observed compliance with infection prevention practices increased from 54.2% to 87.5% (p < 0.001). At 3-month follow-up, knowledge retention remained high: 82.1 ± 7.4, and practice compliance sustained at 83.4%. HCAI incidence decreased from 12.4 to 6.8 per 1,000 patient-days (p = 0.002). Conclusions: A structured educational intervention significantly improved nursing knowledge and compliance with HCAI prevention practices in critical care settings. These improvements in knowledge and practice were sustained at 3-month follow-up and were associated with infection reduction. Regular targeted education should be included in ongoing quality improvement activities within intensive care units.